The Social Needs of the Group Members PNM MEKAAR PBB Indah at Ampek Nagari Sub-District - Andriani Andriani; Wisroni Wisroni (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2020)
This article aims to determine parental understanding of the development of emotional problems in children This study is motivated by the high participation of PNM group members Membina Ekonomi Keluarga Sejahtera (MEKAAR) PBB Indah at  Kecamatan Ampek Nagari, suspected caused by the social needs of PNM Mekaar PBB Indah group members. This study aims to describe the need to be accepted, the need to be valued and the need to be included group members of the PNM Mekaar PBB Indah at Kecamatan Ampek Nagari. The type of this study is quantitative descriptive. The population in this study is the all of PNM Mekaar PBB Indah  group members that are 30 persons. The sample is 67% of the population is about 20 persons, with cluster random sampling technique. The data collecting is using questionnaire, and the data collection tool is the list of written statements. The data analysis technique is using percentage formula. The study result shows that  (1) the needs to be accepted by the group members of PNM Mekaar PBB Indah were very fulfilled, (2) the needs to be respect by the group members of PNM Mekaar PBB Indah were very fulfilled, and (3) the need to be included by the group members of PNM Mekaar PBB Indah  very fulfilled.Keywords: Social Needs, Participation